Emerging gherkin industry in India - Prasanna, D G; Singh, Harendra (Indian Horticulture, 2019)
India has emerged as the origin of the finest gherkin cultivation, processing and exporter to the every-growing world requirement. Gherkin cultivation, processing and exports were started in India during the early 1990s with a modest beginning in Karnataka in South India and later extended to Tamil Nadu and Andhra Pradesh and now has reached an impressive tonnage of 2,25,000 tonnes with a value of Rs 700 crore. The export of processed gherkin is done by about 51 companies located in Karnataka, Tamil Nadu and Andhra Pradesh. Gherkins are grown in contact with small and marginal farmers. Currently there are more than 1,00,000 small and marginal farmers who are engaged in production of gherkins. The contract farmers receive all inputs and technical support from the companies and also the farmers are assured guaranteed buy back of the produce at pre-declared prices. Initially processed gherkins were exported in bulk packing and since 2001 gherkins are being exported in "ready-to-eat jars".